Islamic Integration and Tolerance in Community Behaviour; Multiculturalism Model in The Rejang Lebong District - Idi Warsah; Dewi Cahyani; Rahmi Pratiwi (The Pontianak State Institute of Islamic Studies, 2019)
Culture, religion, ethnic, and language diversity are wealth and pride of Indonesian people. It raises the discourse of multiculturalism as a solution. Taking apart from the pros and cons of this discourse as a Western discourse, authors assert that multiculturalism in the Islamic perspective is the sunnatullah and the fact that it cannot be denied. The descriptive study used to describe the tolerance by the Rejang lebong community and the values derived from Islam and the awareness of Multiculturalism. The results show that there is a link between Islam, nationality and diversity, framed in a multicultural model of social life in Rejang Lebong that adheres to religious values, the philosophy of Pancasila and Bhineka Tunggal Ika, and the philosophy of their ancestors, that is Rejang Pat Petulai which is a symbol of community in unity.